Experimental characterisation and numerical modelling of the influence of bondline thickness, loading rate, and deformation mode on the response of ductile adhesive interfaces. (September 2019) - Lißner, M.; Alabort, E.; Cui, H.; Rito, R.; Blackman, B.R.K.; Petrinic, N.
Abstract: A new method for characterising the rate-dependent failure of ductile adhesively bonded structures has been developed and used to investigate the different modes of loading of representative interfaces. Furthermore, experimental observations enabled a newly developed cohesive zone model that captures all critical aspects of the observed and quantified behaviour of the adhesive under consideration. In particular, the model is capable of reproducing the conducted experiments by incorporating both the dependence of the deformation rate and the adhesive thickness. For that, computed tomography of the adhesive interface was used to resolve three-dimensionally the adhesive volume. The volume fraction of microscopic voids in the adhesive was introduced into the model to rationalise the observed dependence of the mechanical response of the adhesive upon its thickness. Finally, the cohesive zone model was proven with mixed-mode fracture experiments which demonstrate the model's ability to simulate more complex deformation regimes.